To Understand and to Misunderstand How Corruption is Measured: Academic Research and the Corruption Perception Index. (18th January 2018) - Gilman, Stuart C.
Abstract : The Transparency International Corruption Perception Index (CPI) is arguably the most well known of all corruption measures. When published it is headline news in half the world. Academic researchers in public administration and policy often reference or utilize the data, especially in comparative studies. Notably, data from the survey are used as an independent variable to explain policy or administrative issues in fields as different as medicine, engineering, and law enforcement. There have been many published criticisms of the methodology to construct the CPI rankings. Few note that the CPI is not itself a survey but a composite of other surveys. This article focuses on the surveys (sub-indicators) that the CPI uses and the questionable quality of their data. Further, it analyses the impact of the index on academic research and the quality of knowledge researchers have about global corruption.